AIDS, politics, and music in South Africa - McNeill, Fraser G., 1977- (New York : Cambridge University Press, 2011)
"This book offers an original anthropological approach to the AIDS epidemic in South Africa by arguing that music is central to understanding how AIDS interventions operate"--Provided by publisher.
Machine generated contents note: 1. Introduction: AIDS, politics and music; 2. The battle for Venda kingship; 3. A rite to AIDS education? Venda girls' initiation and HIV prevention; 4. 'We want a job in the government': motivation and mobility in AIDS peer education; 5. 'We sing about what we cannot talk about': biomedical AIDS knowledge in stanza; 6. Guitar songs and 'sexy women': a folk cosmology of AIDS; 7. 'Condoms cause AIDS': poison, prevention, and degrees of separation; 8. Conclusion.
Includes bibliographical references (p. 251-271) and index.
Keywords: HIV infections -- Prevention -- South Africa; HIV infections -- Social aspects -- South Africa; Music -- South Africa; HIV Infections -- prevention & control -- South Africa; Anthropology, Cultural -- South Africa; Health Knowledge, Attitudes, Practice -- South Africa; Music -- South Africa